Aortic Stiffness: Epidemiology, Risk Factors, and Relevant Biomarkers - Angoff, Rebecca; Mosarla, Ramya C.; Tsao, Connie W. (Frontiers in Cardiovascular Medicine, 2021)
Aortic stiffness (AoS) is a maladaptive response to increased hemodynamic stress, and increased AoS increases afterload for the heart. AoS is a noninvasive marker for cardiovascular health and offers an additional marker for metabolic dysfunction not captured by measurement of peripheral blood pressure. However, there are challenges with implementing AoS as a diagnostic tool as it increases with age and varies amongst races, rendering the establishment of normative values difficult. AoS is associated with lifestyle factors such as alcohol and smoking, as well as hypertension and comorbid conditions including metabolic syndrome and its components. Multiple studies have investigated various biomarkers associated with increased AoS and this area is of particular interest given that these markers can then become specific therapeutic targets in the future. These biomarkers include those involved in the inflammatory cascade, natriuretic peptides and anti-aging genes, and the renin-angiotensin aldosterone system. In the future, targeting AoS rather than blood pressure itself may improve vascular health and outcomes. In this review, we will discuss the current understanding of AoS, measurement of AoS and the challenges in interpretation, associated biomarkers, and possible therapeutic avenues for modulation of AoS.